ANALISIS PENGELOLAAN SAMPAH DI KOTA SUBULUSSALAM - Hasbullah Hasbullah; Taufik Ashar; Nurmaini Nurmaini (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2019)
ABSTRACT Waste is the outcome and activities of human beings. Its existence cannot be avoided so that it has to be managed well because unhygienic waste will cause environmental pollution. There are 126 cubic meters of waste per day transported to the garbage dump in Subulussalam with 42% of services of the total of 542 cubic meters per day. The objective of the research was to analyze Waste Management in Subulussalam, in 2017.The research used descriptive method by conducting in-depth interviews with 10 respondents. The data were obtained from the Sanitation Agency and gathered by using questionnaires, observation, and documentary study.The result of the research showed that organic waste (70%) was more than the waste from batteries (0.02%). The income and retribution obtained from waste management in Subulussalam increased to 25.2% each year. Facility and infrastructure indicated that waste transportation from the people’s homes used pushcarts (69.2%) since their houses were far from the main street and served by workers manually, while 30.7% were transported by garbage trucks.It is recommended that the City Administration promote the program which encourages waste recycling in order to decrease the waste volumes to the garbage dump and encourage compost making program, the stem of discriminating, collecting, transporting, and dumping waste by adding garbage trucks and workers. Keywords: Analysis, Waste Management, Landfill